Magnetic resonance elastography predicts advanced fibrosis in patients with nonalcoholic fatty liver disease: A prospective study. Issue 6 (29th October 2014) - Loomba, Rohit; Wolfson, Tanya; Ang, Brandon; Hooker, Jonathan; Behling, Cynthia; Peterson, Michael; Valasek, Mark; Lin, Grace; Brenner, David; Gamst, Anthony; Ehman, Richard; Sirlin, Claude
<x xml:space="preserve">Abstract</x> Retrospective studies have shown that two‐dimensional magnetic resonance elastography (2D‐MRE), a novel MR method for assessment of liver stiffness, correlates with advanced fibrosis in patients with nonalcoholic fatty liver disease (NAFLD). Prospective data on diagnostic accuracy of 2D‐MRE in the detection of advanced fibrosis in NAFLD are needed. The aim of this study is to prospectively assess the diagnostic accuracy of 2D‐MRE, a noninvasive imaging biomarker, in predicting advanced fibrosis (stage 3 or 4) in well‐characterized patients with biopsy‐proven NAFLD. This is a cross‐sectional analysis of a prospective study including 117 consecutive patients (56% women) with biopsy‐proven NAFLD who underwent a standardized research visit: history, exam, liver biopsy assessment (using the nonalcoholic steatohepatitis Clinical Research Network histological scoring system), and 2D‐MRE from 2011 to 2013. The radiologist and pathologist were blinded to clinical and pathology/imaging data, respectively. Receiver operating characteristics (ROCs) were examined to assess the diagnostic test performance of 2D‐MRE in predicting advanced fibrosis. The mean (± standard deviation) of age and body mass index was 50.1 (± 13.4) years and 32.4 (± 5.0) kg/m2, respectively. The median time interval between biopsy and 2D‐MRE was 45 days (interquartile range: 50 days). The number of patients with fibrosis stages 0, 1, 2, 3, and 4 was 43, 39, 13, 12, and 10, respectively. The area under the ROC curve for 2D‐MRE discriminating advanced fibrosis (stage 3‐4) from stage 0‐2 fibrosis was 0.924 (P < 0.0001). A threshold of >3.63 kPa had a sensitivity of 0.86 (95% confidence interval [CI]: 0.65‐0.97), specificity of 0.91 (95% CI: 0.83‐0.96), positive predictive value of 0.68 (95% CI: 0.48‐0.84), and negative predictive value of 0.97 (95% CI: 0.91‐0.99). Conclusions: MRE is accurate in predicting advanced fibrosis and may be utilized for noninvasive diagnosis of advanced fibrosis in patients with NAFLD. (Hepatology 2014;60:1919–1927)